Enterprise internationalisation performance evaluation model based on artificial neural network. (10th August 2020) - Yang, Guojun; Zhou, Xiaohu; Liang, Zhiyao
The internationalisation performance of enterprises has been affected by many factors. Designing scientific and effective evaluation index system and conducting comprehensive evaluation are important means to help international enterprises to evaluate their internationalisation performance reasonably. This paper comprehensively reviews the research findings of factors influencing internationalisation performance and indexes at home and abroad, focusing on two quantifiable factors of financial performance and structural proportion, and constructs a hierarchy of internationalisation performance evaluation index system. Secondly, artificial neural network (ANN) is used for adaptive training to obtain the optimised connection weights. Finally, the data of some enterprises' internationalisation performance indexes are collected for empirical research to illustrate the rationality and effectiveness of the method.